Ecological innovations as a chance for sustainable development - directions and obstacles in their implementation = Innowacje ekologiczne szansą dla zrównoważonego rozwoju - kierunki i przeszkody implementacji - Zarębska, Joanna; Michalska, Monika (Zielona Góra: Faculty of Economics and Management Press)
Ecological innovations (eco-innovations) can be considered from the standpoint of innovations implemented within the company in order to: improve organizational and management methods, production process, products, marketing, external relations with the environment and society. They are also a chance for professional development (the so-called green jobs) or can be viewed in terms of consumer interest. Consumer interest in ecoinnovations, and subsequently growth in sales of products and services, influence the effectiveness of innovations and worthiness of their further funding.
Keywords: zrównoważony rozwój; ekoinnowacyjne produkty; zielone miejsca pracy; zarządzanie środowiskowe; sustainable development; ecoinnovative products; ecologically innovative products; green jobs; environmental management